Oral administration of Porphyromonas gingivalis to mice with diet-induced obesity impairs cognitive function associated with microglial activation in the brain - Kana Oue; Yosuke Yamawaki; Kazuhisa Ouhara; Eiji Imado; Tetsuya Tamura; Mitsuru Doi; Yoshitaka Shimizu; Mitsuhiro Yoshida; Noriyoshi Mizuno; Norimitsu Morioka; Takashi Kanematsu; Masahiro Irifune; et al. (Journal of Oral Microbiology)
Objective Both periodontal disease and obesity are risk factors for dementia, but their links to 1brain function remain unclear. In this study, we examined the effects of oral infection with a periodontal pathogen on cognitive function in a mouse model of obesity, focusing on the roles of microglia.Methods To create a mouse model of diet-induced obesity and periodontitis, male C57BL/6 J mice were first fed a high-fat diet containing 60% lipid calories for 18 weeks, beginning at 12 weeks of age, to achieve diet-induced obesity. Then, Porphyromonas gingivalis administration in the oral cavity twice weekly for 6 weeks was performed to induce periodontitis in obese mice.Results Obese mice orally exposed to P. gingivalis showed cognitive impairment in the novel object recognition test. Increased expression levels of inflammatory cytokines (e.g. interleukin-1β and tumor necrosis factor-α) were observed in the hippocampus of P. gingivalis-treated obese mice. Immunohistochemical analysis revealed that microglia cell body size was increased in the hippocampus and prefrontal cortex of P. gingivalis-treated obese mice, indicating microglial activation. Furthermore, depletion of microglia by PLX3397, a colony-stimulating factor 1 receptor inhibitor, ameliorated cognitive dysfunction.Conclusion These results suggest that microglia mediate periodontal infection-induced cognitive dysfunction in obesity.